ANALISIS KORELASI KEHADIRAN DENGAN NILAI AKHIR MAHASISWA PADA MATA KULIAH STATISTIK PENDIDIKAN GEOGRAFI - Sasmita, Anggit (Universitas Khairun, 2023)
This research aims to analyze the correlation between students' attendance and their final grades in the course of Geography Education Statistics. The data used is primary data, which includes the attendance and final grades of students enrolled in the Geography Education Statistics course in the even semester of the 2022/2023 academic year. The statistical analysis method employed is the calculation of Pearson's correlation coefficient using the JASP software application. The research results indicate a fairly significant correlation between the level of student attendance and the final grades they achieve, as demonstrated by an r-value of 0.729 with a significance level of 5%. The calculated r-value falls between -1 and +1, indicating a positive or direct relationship between the two variables. In other words, the higher the number of students attendance, the better the final grades they obtain. The Correlation's Plot shows some data points that do not align with the positive linear trend, suggesting that some students with high attendance do not necessarily achieve high final grades. This indicates that factors other than attendance also influence final grades, such as students' level of comprehension and the completeness of assignments.Â Keywords: Pearson's Correlation Analyzes, attendance, final grade